Kinetic study on the non-isothermal crystallization of Gd53Al24Co20Zr3 bulk metallic glass - 庄艳歆 邢鹏飞 段同飞 史宏宇 赫冀成 (Journal of rare earths, 2011)
Gd-based bulk metallic glass has drawn strong attention because of its large magnetic entropy changes. Thermal stability of metallic glass is a very important issue for its application. In the paper, crystallization behavior of Gd53Al24Co20Zr3 bulk metallic glass was investigated using non-isothermal differential scanning calorimetric （DSC） technique. Attention was given to the analytic details. The crystallized volume fractions as a function of temperature were derived from the DSC signals, where heat capacity change between amorphous phase and crystalline phase was considered. The local activation energies at different crystallized volume fraction were estimated using Doyle-Ozawa and Agrawal methods. The results suggested that the Doyle-Ozawa equation was appropriate to get local activation energy due to its simplicity and accuracy. The local activation energy depended on the crystallized volume fraction. Function reflecting crystallization mechanism was also deduced. The crystallization mechanism of the Gd-based bulk metallic glass was discussed.